Question-Answer Relationship Strategy to Improve Students’ Reading Comprehension Through Narrative Text - Rahmadayani, Nur Fajriah; Hudriati, Andi; Sulastri, Sulastri (Fakultas Sastra Universitas Muslim Indonesia, 2024)
Reading is not an easy task to do. Reading is a thinking process. The act of recognizing words requires the interpretation of graphic symbols. This study aims to determine the implementation and students’ obstacles to using the Question-Answer Relationship (QAR) strategy to improve students' reading comprehension skills through narrative text. This study used a quantitative method with a pre-experimental class with one group pretest-posttest design. This research was conducted in class VIII SMP Negeri 8 Makassar which involved 35 students as the research sample. The researcher used reading tests and questionnaires as instruments for data collection. The results showed that the use of the QAR strategy could improve students' reading comprehension skills significantly. The students’ average score on the pre-test was 39.14 After applying the QAR strategy, the students’ average score on the post-test increased to 69.14. There was an improvement of 57% from the pre-test to the post-test. The researcher concluded that the use of a Question-Answer Relationship (QAR) strategy could improve the students’ activeness in teaching learning process.